(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to examine the relationship between knowledge and attitudes regarding the prevalence of hypertension among older adults. The method used is an analytical survey with a cross-sectional approach. The results of the study showed that there was a relationship between knowledge and the incidence of hypertension in the elderly with a p-value of 0.004 and there was a relationship between attitudes and the incidence of hypertension in the elderly with a p-value of 0.003. Conclusion, there is a significant relationship between knowledge and attitudes with the incidence of hypertension in the elderly. Keywords: Hypertension, Elderly, Knowledge, Attitude